Leading people expert solutions to everyday challenges (Pocket mentor series., 2006)
Today's leaders don't use command-and-control. Instead, they leverage their communication, collaboration, and conflict-resolution skills to inspire employees to ever higher levels of performance. Packed with practical tools and expert advice, Leading People shows managers how to bring out the best in their team.